2017
DOI: 10.1002/sim.7431
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 20 heterogeneity variance estimators in statistical synthesis of results from studies: a simulation study

Abstract: When we synthesize research findings via meta-analysis, it is common to assume that the true underlying effect differs across studies. Total variability consists of the within-study and between-study variances (heterogeneity). There have been established measures, such as I , to quantify the proportion of the total variation attributed to heterogeneity. There is a plethora of estimation methods available for estimating heterogeneity. The widely used DerSimonian and Laird estimation method has been challenged, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 47 publications
2
69
2
Order By: Relevance
“…Our finding on the Paule‐Mandel estimator disagrees with a study that compared 20 heterogeneity variance estimators. In this study, it is concluded that the Paule‐Mandel estimator “provides good estimation behaviour but not markedly better than the other alternatives.” In our study, the Paule‐Mandel estimator outperformed the DerSimonian‐Laird method in all scenarios, in particular if combined with t ‐distributed confidence intervals. The main reasons are probably that in contrast to our simulation only scenarios with 5 to 30 studies were simulated and only confidence intervals based on the normal approximation were used in the comparison.…”
Section: Discussionmentioning
confidence: 62%
“…Our finding on the Paule‐Mandel estimator disagrees with a study that compared 20 heterogeneity variance estimators. In this study, it is concluded that the Paule‐Mandel estimator “provides good estimation behaviour but not markedly better than the other alternatives.” In our study, the Paule‐Mandel estimator outperformed the DerSimonian‐Laird method in all scenarios, in particular if combined with t ‐distributed confidence intervals. The main reasons are probably that in contrast to our simulation only scenarios with 5 to 30 studies were simulated and only confidence intervals based on the normal approximation were used in the comparison.…”
Section: Discussionmentioning
confidence: 62%
“…Any τ 2 estimator can be used when computing a WTz CI. 50,113,114 This method often has coverage probability considerably below nominal 0.95 level 14,15,45,[115][116][117][118][119][120][121] when k is small and/or τ 2 is large. 13,45,52,79,118,119,[122][123][124][125] Brockwell and Gordon 13 stated that the greatest source of error in the method is the use of a normal approximation for μ̂R E .…”
Section: Resultsmentioning
confidence: 99%
“…And θj=θ+εj, εj~N(),0τ2, where τ 2 is the between‐study variance. Numerous estimators exist for τ 2 , with the one most commonly used proposed by DerSimonian and Laird: τtruêDL2=Qwtruê()k1j=1kwtruêjj=1kwtruêj2/j=1kwtruêj, Qwtruê=j=1kwtruêjtrueγ̂1jtrueγ̂12, where wtruêj=1/σj2, k is the number of studies, and γtruê1=j=1kwtruêjY´jj=1kwtruêj is the overall exposure effect estimate under a fixed‐effect approach with Y´j=θ+ej.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the correct specification of the 1‐stage model is critical, and guides and software to aid researchers in this are available . Fewer modelling options are available for two‐stage analysis, and they are mainly around the choice of the second step model, fixed effect, or one of the numerous random‐effects options . A well‐developed implementation of a two‐stage analysis is available in Stata, with the less flexible ipdmeta command, which can only analyse a continuous outcome, available in R software .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation